2020
DOI: 10.1111/sltb.12630
|View full text |Cite
|
Sign up to set email alerts
|

Traumatizing Oneself—Deep Wrist Injuries Self‐Inflicted with Suicidal Intention are Associated with More Severe PTSD Symptomatology than Similar Injuries from Accidents

Abstract: Objective As suicide attempts by definition entail at least some threat to physical integrity and life, they theoretically qualify as an A1 criterion for posttraumatic stress disorder (PTSD). This study uses the unique opportunity of deep wrist injuries to quantify the effect of intentionality on PTSD rates by comparing suicide attempt survivors with patients who sustained accidental injuries similar in mechanism, localization, and extent. Method Patients who had been admitted with an acute deep wrist injury f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…However, the context of when these associations are examined and who is included in the sample makes comparisons difficult. Given the similarity in samples of suicide attempt survivors, our results build most closely on the findings by Westermair et al (2020) by integrating suicide‐specific constructs associated with the IPTS into our design.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the context of when these associations are examined and who is included in the sample makes comparisons difficult. Given the similarity in samples of suicide attempt survivors, our results build most closely on the findings by Westermair et al (2020) by integrating suicide‐specific constructs associated with the IPTS into our design.…”
Section: Discussionsupporting
confidence: 71%
“…Although understudied in the field of suicide prevention (Stanley et al, 2019), there is reason to believe that medically serious suicide attempts and resulting treatment may be experienced as traumatic by the survivor. A recent study by Westermair et al (2020) found that intentional self‐injury by deep wrist laceration was associated with greater PTSD symptomatology years later in comparison with those treated for similar unintentional injuries. The authors describe the extent to which characteristics of the attempt, such as deciding against dying and needing to treat one's own physical injuries, may be experienced as traumatic.…”
Section: Introductionmentioning
confidence: 99%
“…Children who have experienced the death by suicide of a parent or a sibling are at elevated risk for psychiatric symptoms, especially depression, posttraumatic stress disorder, and social maladjustment (Pfeffer et al, 1997(Pfeffer et al, , 2000Sethi & Bhargava, 2003). Adult survivors of suicide have been found to be susceptible to developing trauma symptoms, including a preoccupation with and/or avoidance of reminders about suicide, terror-filled recollections, emotional withdrawal, and hyper arousal, among others (Hibberd et al, 2010;Westermair et al, 2020). In a study by Stanley, Hom, et al (2019), over one-quarter of adult suicide attempt survivors (27.5%) reported post-traumatic stress disorder symptoms related to their suicidal behaviors.…”
Section: Trauma Among Suicide Survivors and Suicidal Youthmentioning
confidence: 99%